1996
DOI: 10.1136/bjo.80.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic study of monofilament suture knots.

Abstract: Aims/Background-Interrupted corneal sutures are used routinely by many cataract and corneal surgeons. A slim compact knot facilitates burial and allows atraumatic suture removal, with decreased risk of wound dehiscence. The size and morphology of knots tied in different configurations were investigated. Methods-10-0 nylon suture material was used to tie knots on porcine corneal cataract sections using 2/1/1 (reef and granny), 3/1/1, and 1/1/1/1 (slip knot) configurations. 10-0 Mersilene was used to tie 2/1/i r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Hammond et al demonstrated with electron microscopy that a 2-1-1 nylon reef knot was a slim knot that allowed easier knot burial and atraumatic suture removal, thus reducing the risk of wound dehiscence. 15 The way in which the knots are buried can determine how easily they can be removed later on. It is generally undesirable to drag the knot through the graft–host interface, and we would recommend that the knots should not be buried at the interface.…”
Section: Discussionmentioning
confidence: 99%
“…Hammond et al demonstrated with electron microscopy that a 2-1-1 nylon reef knot was a slim knot that allowed easier knot burial and atraumatic suture removal, thus reducing the risk of wound dehiscence. 15 The way in which the knots are buried can determine how easily they can be removed later on. It is generally undesirable to drag the knot through the graft–host interface, and we would recommend that the knots should not be buried at the interface.…”
Section: Discussionmentioning
confidence: 99%
“…The suture knot is believed to be the most irritant part of the suture and offers the greatest impediment to suture burial. A 2/1/1 nylon reef knot has been shown to produce the smallest knot size4 with consequent ease in burial. We have preferred a 3/2/1 configuration, which gives a leading arrowhead configuration to facilitate burial.…”
mentioning
confidence: 99%
“…They induce minimal torsion of the graft and allow for selective removal to manage postgraft astigmatism. However, if tied with differing tensions, they can induce more astigmatism, and the larger number of knots can be detrimental as stated above 47…”
mentioning
confidence: 99%